Men's preferences for image-guidance in prostate radiation therapy: A discrete choice experiment. (February 2022) - Brown, Amy; Pain, Tilley; Tan, Alex; Anable, Lux; Callander, Emily; Watt, Kerrianne; Street, Deborah; De Abreu Lourenco, Richard
Highlights: Discrete Choice Experiments can robustly capture patient preferences in oncology. The patient experience of prostate cancer IGRT solutions varies. Less cost and pain are preferred for IGRT over other attributes such as side effects. Prostate cancer patients value accuracy more than the general population. Knowledge of preferences empowers clinicians for patient-centred care. Abstract: Introduction: There are several options for real-time prostate monitoring during radiation therapy including fiducial markers (FMs) and transperineal ultrasound (TPUS). However, the patient experience for these procedures is very different. This study aimed to determine patient preferences around various aspects of prostate image-guidance, focusing on FMs and TPUS. Methods: A discrete choice experiment (DCE) was conducted, describing the image-guidance approach by: pain, cost, accuracy, side effects, additional appointments, and additional time. Participants were males with prostate cancer (PCa) and from the general Australian population. A DCE survey required participants to make hypothetical choices in each of 8 choice sets. Multinomial logit modelling and Latent Class Analysis (LCA) were used to analyse the responses. Marginal willingness to pay (mWTP) was calculated. Results: 476 respondents completed the survey (236 PCa patients and 240 general population). The most important attributes for both cohorts were pain, cost and accuracy ( p < 0.01). PCa patients were willing to pay more to avoid the worst pain than the general population, and willing to pay more for increased accuracy. LCA revealed 3 groups: 2 were focused more on the process-related attributes of pain and cost, and the third was focused on the clinical efficacy attributes of accuracy and side effects. Conclusion: Both cohorts preferred less cost and pain and improved accuracy, with men with PCa valuing accuracy more than the general population. In addition to the clinical and technical evidence, radiation oncology centres should consider the preferences of patients when considering choice of image-guidance techniques.